Development of Increasing Business Competitiveness In Betoyoguci Village Gresik Regency - Suaibatul Aslamiyah (OJS Universitas Muhammadiyah Gresik, 2022)
Since March 2020, the COVID-19 pandemic that has hit Indonesia has not ended. The existence of the micro, small and medium enterprise (MSME) sector which plays a very important role in economic development and growth is the most affected by this pandemic. Various problems experienced by MSMEs include decreased sales, capital, hampered distribution, difficulty in raw materials, decreased production and layoffs of workers which pose a threat to the national economy. In addition, MSMEs lack resilience and flexibility in dealing with this pandemic, due to several things such as the low level of digitalization, difficulties in accessing technology and a lack of understanding of strategies to survive in business (OECD, 2020). The purpose of the service activity is to develop the competitiveness of MSMEs through information technology and innovation in Betoyoguci Village, Gresik Regency. The method used is Participatory Rural Appraisal (PRA), namely approaches and techniques for involving the community in thought processes that take place during planning, implementing, as well as monitoring, and evaluating community development programs (Hamid, 2018). The activity was carried out in a hybrid manner, with 24 offline participants at the Betoyoguci Village meeting hall. To make it easier for coaching, in addition to explaining the forms of innovation that can be done during the COVID-19 pandemic, activities are supported by the practice of using information technology with the Shopee E-Commerce platform, starting from downloading in the appstore to uploading products, so that an increase in the ability of participants can be obtained. still survive during the pandemic that is still ongoing today.